Oral Cryotherapy: Prevention of Oral Mucositis and Pain Among Patients With Colorectal Cancer Undergoing Chemotherapy - Nawi, Ros Idayu Mat; Chui, Ping Lei; Ishak, Wan Zamaniah Wan; Hsien Chan, Caryn Mei (Oncology Nursing Society, 2018)
BACKGROUND: Evidence remains mixed on the benefits of oral cryotherapy in the prevention of oral mucositis and pain associated with fluorouracil-based chemotherapy. OBJECTIVES: The intent of this article is to evaluate the effect of oral cryotherapy on the prevention of oral mucositis and pain among patients with colorectal cancer undergoing fluorouracil-based chemotherapy. METHODS: Using an experimental study design, the authors randomly assigned 80 patients to either the intervention (n = 40) or usual care group (n = 40). Intervention group participants received oral cryotherapy in the form of ice chips held in their mouths during chemotherapy infusion. Both groups used sodium bicarbonate mouthwash postchemotherapy until the next cycle. FINDINGS: In the usual care group, most participants reported grade 2 (moderate to life-threatening) or greater mucositis. Pain associated with mucositis was lower using oral cryotherapy, with the majority of participants in the intervention group reporting no pain.